2016
DOI: 10.5935/0103-5053.20160156
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation Reactions of Rhodamine B and 6G as Revealed by High Accuracy Orbitrap Tandem Mass Spectrometry

Abstract: Correct interpretation of mass spectra is essential to our understanding of the ion chemistry occurring in the gas phase inside mass spectrometers and for constructing a solid knowledge from which mass spectrometry (MS) data of novel molecules will be interpreted. Assignments of product ions leading to incorrect dissociation mechanisms can also be dangerous in several disciplines such as in forensic chemistry and clinical diagnostics. Main fragmentation routes for rhodamines B and 6G were investigated by high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…4 b). Consistent with previous studies 19 , 20 , the linearity of the precursor ions for dox and rhodamine were found at m/z 544 Da and 443 Da, respectively. We later used this LC/MS standard curves to extrapolate the quantitative capability using the spectral microscopy.…”
Section: Resultssupporting
confidence: 91%
“…4 b). Consistent with previous studies 19 , 20 , the linearity of the precursor ions for dox and rhodamine were found at m/z 544 Da and 443 Da, respectively. We later used this LC/MS standard curves to extrapolate the quantitative capability using the spectral microscopy.…”
Section: Resultssupporting
confidence: 91%
“…S15 and S16. [65][66][67][68] In the case of MB, we identified the thionin intermediate (m/z = 228) after 100 min of reaction, suggesting that the MB degradation occurs via the auxochrome group degradation, i.e. via demethylation cleavage during the photo catalytic degradation 69,70 -Fig.…”
Section: Photocatalytic Activitymentioning
confidence: 93%
“…To quantify the maximum and minimum mass spectrometry concentrations limits of the selected chemicals, Q-TOF MS and LC/MS was conducted. For Q-TOF MS method, Rhodamine was by injected at different concentrations (Table 2) and by checking the molecular mass the maximum concentration limit to detect at 5 nM (Fig 11), while 0.2 nM is the minimum concentration with precursor ion at m/z 443 Da which consistent with previous studies (Ferreira et al, 2017) (Fig 12).…”
Section: Q-tof Ms and Lc/mssupporting
confidence: 84%